1999
DOI: 10.1680/macr.1999.51.6.415
|View full text |Cite
|
Sign up to set email alerts
|

Strut and tie models for analysis/design of external beam—column joints

Abstract: Strut and tie models have been developed for external beam±column joints with and without joint stirrups. The modelling is fraught with difficulties that include determining forces at joint boundaries and strut dimensions. In view of these difficulties, it was found necessary to define strut widths empirically. Test data were used to show that stirrups can increase joint shear strength by less than their yield capacity. The model accounts for this by using a stiffness analysis to determine the proportion of jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Second, the post-tensioning compressive force applied to the columns may have assisted the behaviour of the joints, as suggested by Paulay (1989), although counter-evidence exists that questions the existence of this beneficial effect (Kim and LaFave 2007). Besides the aforementioned references, many other studies focus on the seismic behaviour of the beam-column joint (Paulay and Park 1984;Ichinose 1991;Vollum and Newman 1999;Bakir and Boduroglu 2006;Bakir 2003;Vollum and Parker 2008). The columns remained in the elastic range with minor cracking.…”
Section: Overall Performancementioning
confidence: 99%
“…Second, the post-tensioning compressive force applied to the columns may have assisted the behaviour of the joints, as suggested by Paulay (1989), although counter-evidence exists that questions the existence of this beneficial effect (Kim and LaFave 2007). Besides the aforementioned references, many other studies focus on the seismic behaviour of the beam-column joint (Paulay and Park 1984;Ichinose 1991;Vollum and Newman 1999;Bakir and Boduroglu 2006;Bakir 2003;Vollum and Parker 2008). The columns remained in the elastic range with minor cracking.…”
Section: Overall Performancementioning
confidence: 99%
“…7 All the models, tend on average to overestimate the strength of Parker and Bullman's 12 specimens 4b to 4f, which failed at comparatively low joint shear forces, 6,7,14 probably influenced by the high bearing stresses inside the bends. Separate statistical analyses are given in Table 1 for joints with joint stirrups and in Table 1 for joints without shear reinforcement excluding the specimens of Parker and Bullman, 12 which failed at comparatively low joint shear strengths.…”
Section: Comparison With Test Data and Other Design Methodsmentioning
confidence: 94%
“…5 The current paper presents a rational strut and tie model for the design of external beam-column joints which is consistent with the recommendations of EC2. 3 The model is a considerable improvement on Vollum and Newman's 6 earlier stut and tie model (STM) for external beam column joints which dimensioned the struts using non-rational calibration factors derived from back analysis of test data. The method is validated with test data and is shown to give consistent and safe designs.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining parameters are still being debated. Some researchers (Bakir and Boduroglu, 2002;Hegger et al, 2003;Kim and LaFave, 2008;Parker and Bullman, 1997;Paulay and Priestley, 1992;Sarsam and Phipps, 1985;Vollum and Newman, 1999) have proposed inconsistent contributions of joint shear reinforcement in the shear strength of beamcolumn joints while some (Marques and Jirsa, 1975;Meinheit and Jirsa, 1977;Pantazopoulou and Bonacci, 1992) have indicated that column axial load has no coherent effect on joint shear strength. Clyde et al (2000) reported that column axial load helped to improve the joint shear strength while Park and Mosalam (2012) showed that joint shear strength is not clearly affected by column axial stress up to 0 : 2 f 9 c :…”
Section: Parameters Of Influence In Beam-column Connectionsmentioning
confidence: 99%